2007
DOI: 10.1007/s10967-006-6907-z
|View full text |Cite
|
Sign up to set email alerts
|

Complexation of plutonium(IV) with sulfate at variable temperatures

Abstract: The complexation of plutonium(IV) with sulfate at variable temperatures has been investigated by solvent extraction method. A NaBr03 solution was used as holding oxidant to maintain the plutonium(IV) oxidation state throughout the experiments. The distribution ratio of Pu(1V) between the organic and aqueous phases was found to decrease as the concentrations of sulfate were increased. Stability constants of the 1 : 1 and 1:2 Pu(IV)-HS0; complexes, dominant in the aqueous phase, were calculated from the effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 17 publications
1
19
0
2
Order By: Relevance
“…In contrast to the cation effect, the addition of certain anions had a significant influence on K d values; the sorption of Pu was strongly influenced by adding SO 4 2− and CO 3 2− . A similar result was reported by Xia et al [36], who concluded that "the distribution ratio of Pu(IV) between the organic and aqueous phases was found to decrease as the concentrations of sulfate were increased". On the other hand, the effects on Pu sorption by NO 3 − and Cl − were weak.…”
Section: Influence Of Different Ions (Cations and Anions)supporting
confidence: 87%
“…In contrast to the cation effect, the addition of certain anions had a significant influence on K d values; the sorption of Pu was strongly influenced by adding SO 4 2− and CO 3 2− . A similar result was reported by Xia et al [36], who concluded that "the distribution ratio of Pu(IV) between the organic and aqueous phases was found to decrease as the concentrations of sulfate were increased". On the other hand, the effects on Pu sorption by NO 3 − and Cl − were weak.…”
Section: Influence Of Different Ions (Cations and Anions)supporting
confidence: 87%
“…''H 2 O'' would also include hydrogen bonded proton networks, giving Pu-O bond lengths differing from those found in solution and contributing to the asymmetric/anharmonic O distribution around the 2.33 Å principal crystallographic shell. Inclusion of protonated species in the initially formed precipitates would be expected, and their subsequent elimination and ordering of the lattice is undoubtedly related to the ripening process [4,[35][36][37][38] that causes the solubility constants to change by orders of magnitude over time. These directly coordinated near neighbor O shells with shorter Pu-O distances are supplemented by longer Pu-O distances that result from the mirroring of these displacements on the neighboring Pu atoms.…”
Section: Complex Pu-o Distributions In Conventionally Prepared Materialsmentioning
confidence: 99%
“…In recent studies, equilibrium constants and the enthalpy of complexation have been determined for U(VI)/sulfate complexes by spectrophotometry (16), for Np(V)/sulfate complexes by spectrophotometry (14,18) and solvent extraction (13), and for Pu(IV)/sulfate complexes by solvent extraction (19), in the temperature range from 25 to 70 o C. The data are summarized in Table III and discussed below. …”
Section: Complexation Of Actinides With Sulfate At Variable Temperaturesmentioning
confidence: 99%
“…The complexation of plutonium(IV) with sulfate at variable temperatures from 25 o C to 55 o C has been investigated by the solvent extraction method (19). The decrease of the distribution ratio of Pu(IV) between the organic and aqueous phases was interpreted as being due to the formation of 1:1 and 1:2 Pu(IV)-SO 4 2-complexes in the aqueous phase and the stability constants of Pu(SO 4 ) 2+ and Pu(SO 4 ) 2 (aq) at different temperatures were accordingly calculated.…”
Section: Pu(iv)/sulfatementioning
confidence: 99%
See 1 more Smart Citation